ENHANCING EIGHTH-GRADE STUDENT’S READING COMPREHENSION USING RECIPROCAL TEACHING METHOD AT SMP MUHAMMADIYAH AT TANWIR METRO - Jihan Asri; Bambang Eko Siagiyanto; Fitri Palupi Kusumawati; Eva Faliyanti (English Education Study Program, 2026)
This study focuses on enhancing reading comprehension of descriptive texts among eighth-grade students at Muhammadiyah Junior High School in At Tanwir Metro. The objectives of this study were first to determine whether the Reciprocal Teaching Method can improve the reading comprehension skills of eighth-grade students at SMP Muhammadiyah At Tanwir Metro and second to explore the factors that influence this improvement. This study used the Classroom Action Research (CAR) methodology. This study was conducted at eighth-grade students of Al Fath class at SMP Muhammadiyah At Tanwir Metro, consisting of 30 participants. Data were collected through pre-tests and post-tests (multiple- choice questions on descriptive texts), observation sheets to assess student activities, and questionnaires to collect student responses. This method proved effective, as evidenced by the increase in students' post-test scores from an average of 55.6 in the pre-test, to 66.5 in Cycle I, and reaching 72.16 in Cycle II. The second research question was addressed through qualitative data from observations and questionnaires, revealing that factors such as group discussions, teacher support, active questioning, and vocabulary assistance significantly contributed to students’ progress. Most students responded positively to the method, reporting better comprehension, greater confidence, and a more enjoyable learning experience. Seven out of ten indicators met or exceeded the 70% criterion, confirming that Reciprocal Teaching is a practical, student-centered approach that fosters deeper understanding and active classroom participation.